The teaching training in pedagogy: some reflections around their possibilities and challenges (Revista Internacional de Formação de Professores, 2019)
This article reflects on the pedagogical training, based on the experience of the curriculum implemented in 2003 at the Faculty of Education of the University of Brasília. The study adopts qualitative approach methodology, where it analyzes the intentions expressed in normative documents and the student's vision about the formation, considering its course in the course, in front of the demands of the different fields of action for which the educator is formed. The reflections around this study allow us to rethink the degree in Pedagogy in the perspective of valuing and overcoming the challenges of teaching practice, envisaging training that favors integration between theory and practice.
Keywords: Teacher education. Curriculum. Teaching practice. Teacher knowledge.